The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4081/ija.2011.e18
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation of green biodegradable mulch on melon

Abstract: A two-year research was carried out in 2004-2005 in order to evaluate the effects of biodegradable green mulch on melon (Cucumis melo L. var. reticulatus Naud.) yield and quality. The loss of quality due to the presence of spot caused by the residues of biodegradable plastics was also investigated. The research was conducted over two years, in open field, at S. Piero a Grado, Pisa, Italy, (lat. 43.67498, long. 10.34737), from the beginning of May to the end of July of each year. The films tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
1
18
1
1
Order By: Relevance
“…Our findings concerning the beneficial effect of mulching versus bare soil were also reported in previous studies on open-field and greenhouse vegetables. For instance, melon plants had more fruits and higher fruit mean weight when grown with biodegradable films and LDPE, as compared to bare soil [2]. An increase in marketable yield in the presence of polyethylene and biodegradable (Mater-Bi ® ) films when compared to bare soil was also observed in pumpkin [24], tomato [1,4,25], strawberry [3,26], garlic chives [5], as well as lettuce [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings concerning the beneficial effect of mulching versus bare soil were also reported in previous studies on open-field and greenhouse vegetables. For instance, melon plants had more fruits and higher fruit mean weight when grown with biodegradable films and LDPE, as compared to bare soil [2]. An increase in marketable yield in the presence of polyethylene and biodegradable (Mater-Bi ® ) films when compared to bare soil was also observed in pumpkin [24], tomato [1,4,25], strawberry [3,26], garlic chives [5], as well as lettuce [27].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of this technique in agriculture dates back to the 1970s, and its success is still linked to multiple benefits. In fact, plastic films can: (i) increase soil temperature and keep it constant throughout the first 20-30 cm layer, so that plants' roots develop faster [1,2]; (ii) reduce soil evapotranspiration and preserve moisture; (iii) prevent soil erosion and excessive leaching of nutrients from plants' rhizosphere; and, (iv) improve the performance of plants in a quantitative and qualitative manner [1,[3][4][5]. In addition, mulching films suppress weeds growth, protect crops against pests and various diseases, and reduce the use of pesticides and herbicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have recently analysed the agronomic and environmental performance of paper mulch (Martin-Closas et al, 2003;Moreno et al, 2013;Haapala et al, 2014), polyethylene with additives for degradation or biodegradable films (Filippi et al, 2011;Saraiva et al, 2012;Benincasa et al, 2014). By conducting field experiments, these studies showed that these potential substitutes of conventional films offer the advantage of degrading into non-toxic components.…”
Section: Introductionmentioning
confidence: 99%
“…However, solarisation, cultivar disease resistance, and the use of grafted plants may help limit these problems (Alan et al, 2007;Castronuovo et al, 2005;Tamietti and Valentino, 2006;Trionfetti Nisini et al, 2002). In contrast to high tunnels, either low tunnels, floating row covers or ground mulches are usually disposable and thus expensive (cost of material, setup and disposal), although biodegradable films are now available which would help avoid at least usage/disposal costs (Filippi et al, 2011;Vox et al, 2005;Waterer, 2010). In any case, the profit margin of using plastic protections just for a warming effect may be quite small, particularly when considering that cheap products may often be gathered from nearby cultivation areas with milder spring climates.…”
Section: Introductionmentioning
confidence: 99%